Current Advancements and Applications of Machine Learning Methods - Amit Kumar Balyan, Sanjeev Kumar Sharma (International Journal of Control and Automation, 2020)
Machine learning seems to be an artificial intelligence research area that really provides computers the ability to acquire without express data analysis. This, therefore, focuses primarily on automating its construction of intellectual models that enable strategic planning. Machine learning methodologies have all the performance of fast learning and may also gain knowledge from either the data, recognize issues and make judgments to minimal physical involvement. The whole reliability of machine learning draws researchers extremely to use that in different disciplines. We introduce throughout this survey article 'review of recent advancements as well as machine learning methods applications.' The whole document encompasses a comprehensive analysis of different methodologies for machine learning as well as the applications, but also recommendations in recent developments within these techniques.